A limit theorem for the number of sign changes for a sequence of one-dimensional diffusions - Kulik, A.M. (Інститут математики НАН України, 2008)
The (normalized) number of sign changes for a weakly convergent sequence of onedimensional diffusion processes is considered. The limit theorem for this number is established.